Elastic modulus tailoring in CH3NH3PbI3 perovskite system by the introduction of two dimensionality using (5-AVA)2PbI4. (August 2021) - Rathore, Sudharm; Han, Guifang; Kumar, Anshuman; Leong, Wei Lin; Singh, Aparna
Highlights: Elastic modulus determination of perovskite thin film using nanoindentation. Experimental results are corroborated by density functional theory calculations. No quasi-2D perovskite observed in mixed 2D-3D perovskites. Elastic Modulus of 2D perovskite is less than half of the modulus of 3D perovskite. Elastic modulus of the mixed perovskite is close to the lower bound for the mixture. Abstract: The stiffness of the perovskite active layer plays a critical role in influencing the flexibility of a solar cell. This is one of the important parameters which must be considered while deciding the architecture of the flexible device. Till now, there have been limited studies on the mechanical properties of 2D and 3D perovskite thin films. In this study, we report the very first time, the elastic modulus of the most commonly used 3D perovskite i.e. methylammonium lead iodide (MaPbI3 ), the pure 2D perovskite (5-AVA)2 PbI4 which is based on 5-aminovaleric acid (5-AVA) cation as well as the 2D-3D mixed perovskites thin films through nanoindentation technique. The elastic modulus for the 3D perovskite has been found to be around 16.5 GPa, while it decreases to 6.3 GPa for pure 2D perovskite. The experimental results have also been corroborated by density functional theory calculations done for the 2D and 3D perovskite. The 2D perovskite shows a much lower modulus than the 3D perovskite and can be used within a 2D-3D mixture for improving the mechanical flexibility of the active layer. Also, it is well established that 2D perovskites are much more stable against moisture as compared to their 3D counterparts due to the presence of hydrophobic organic alkyl ammonium cation. Thus, the device containing an active layer comprising of a mixture of 3D and 2D perovskite can be used to improve the environmental stability of the overall device in addition to achieving mechanical durability.